Ulıwma bilim beriw mekteplerinde klasstan tısqarı jumıslardı shólkemlestiriwdiń ayırım máseleleri - Qurmanov, A.; Shamuratova, T.; Amanbaev, M.; Yuldasheva, N. (ILIM hám JÁMIYET, 2020)
The article deals with the education of the young generation in order to prepare highly educated specialists with the help of the effec- tive organization of out-of-class work in secondary educational schools.